2017
DOI: 10.18203/2349-3291.ijcp20172626
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia and raised hematocrit-predictor in dengue hemorrhagic fever

Abstract: Background: This study evaluated the symptoms and routine laboratory investigation to arrive at a bedside diagnosis of dengue hemorrhagic fever and to predict the prognosis on the basis of clinical features and investigation.Methods: This was a prospective study and included children age up to 15 years admitted in the pediatric ward over 2 years period. Dengue fever and dengue hemorrhagic fever were defined according to WHO guidelines.Results: Out of 90 Dengue positive children 44 (48.8%) were of Dengue Hemorr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…High hematocrit points towards plasma leakage from blood capillaries. Our study demonstrated greater than 45 hematocrit in all age groups which is in alignment with other study (21). Hematocrit values are quite helpful in monitoring amount of intravenous fluid and also direct us about the use of blood products if needed in dengue patients.…”
Section: Discussionsupporting
confidence: 91%
“…High hematocrit points towards plasma leakage from blood capillaries. Our study demonstrated greater than 45 hematocrit in all age groups which is in alignment with other study (21). Hematocrit values are quite helpful in monitoring amount of intravenous fluid and also direct us about the use of blood products if needed in dengue patients.…”
Section: Discussionsupporting
confidence: 91%
“…Thrombocytopenia and increments in the hematocrit percentage in DENV-infected patients are considered warning signs by the WHO and correlate with viremia and severity of the clinical presentation of dengue ( WHO, 2009 ; Upadhyay et al., 2017 ; Pathak et al., 2021 ). We observed a correlation of DENV isolates susceptibility to type I interferon antiviral response with the increment of hematocrit percentage and thrombocytopenia ( Figure 5 ), supporting the hypothesis that type I interferon susceptibility of DENV could be a driving factor in the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Increased hematocrit value was found in 88(47%) cases of our dengue children, which was 36% in Upadhya N et al study. 15 Serial hematocrit values may help in increasing or decreasing intravenous fluids and guides us whether blood or blood products are needed or not.A significant number of thrombocytopenic children developed raised hematocrit (Table IV). This finding was consistent with the study of Jayashree K et al 4 Raised hematocrit along with moderate to severe thrombocytopenia was found significant in the development of severe dengueinfection (Table V).…”
Section: Methodsmentioning
confidence: 99%